2019
DOI: 10.1021/acsami.9b09283
|View full text |Cite
|
Sign up to set email alerts
|

Ru(III)-Based Metal–Organic Gels: Intrinsic Horseradish and NADH Peroxidase-Mimicking Nanozyme

Abstract: Highly active, stable, and cost-effective enzyme-mimicking nanomaterials (nanozymes) hold the potential to be an alternative to replace natural enzymes for the catalysis of enzyme-like reactions in various applications. Here, novel 3D ruthenium-based metal−organic gels (Ru-MOGs) with fibrillar network structures have been successfully synthesized using a facile one-step strategy at room temperature. Surprisingly, the developed 3D fibrillar networked Ru-MOGs simultaneously possess intrinsic horseradish peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Metal–organic gels (MOGs) have emerged as a new type of metal–organic hybrid material, and they can be rapidly built up by straightforward self-assembling from metal ions and organic ligands through metal–ligand interactions and intermolecular forces. In particular, MOGs can be obtained by a facile and mild strategy (e.g., neutral condition, relatively low reaction temperature, routine solvents, and short reaction time). Due to the well-defined metal–ligand catalytically active sites, high thermal stability, large surface areas, and unique porous structures, MOGs have been widely applied in the fields of adsorption, catalysis, , drug delivery, sensing, white-light-emitting diodes, and environmental pollution abatement. , Recently, Li’s group employed the silver-based MOG as the solid coreactants to enhance the ECL of Ru­(bpy) 3 2+ for DNA assay, with the MOG being used for the loading of Ru­(bpy) 3 2+ molecules . In addition, Li’s group synthesized terbium metal–organic gels (TOGs) and employed the cathode ECL emission of TOGs for the detection of tetracycline, with TOGs being used as the luminophor .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Metal–organic gels (MOGs) have emerged as a new type of metal–organic hybrid material, and they can be rapidly built up by straightforward self-assembling from metal ions and organic ligands through metal–ligand interactions and intermolecular forces. In particular, MOGs can be obtained by a facile and mild strategy (e.g., neutral condition, relatively low reaction temperature, routine solvents, and short reaction time). Due to the well-defined metal–ligand catalytically active sites, high thermal stability, large surface areas, and unique porous structures, MOGs have been widely applied in the fields of adsorption, catalysis, , drug delivery, sensing, white-light-emitting diodes, and environmental pollution abatement. , Recently, Li’s group employed the silver-based MOG as the solid coreactants to enhance the ECL of Ru­(bpy) 3 2+ for DNA assay, with the MOG being used for the loading of Ru­(bpy) 3 2+ molecules . In addition, Li’s group synthesized terbium metal–organic gels (TOGs) and employed the cathode ECL emission of TOGs for the detection of tetracycline, with TOGs being used as the luminophor .…”
mentioning
confidence: 85%
“…39−41 In particular, MOGs can be obtained by a facile and mild strategy (e.g., neutral condition, relatively low reaction temperature, routine solvents, and short reaction time). Due to the well-defined metal−ligand catalytically active sites, high thermal stability, large surface areas, and unique porous structures, 42 MOGs have been widely applied in the fields of adsorption, 39 catalysis, 43,44 drug delivery, 45 sensing, 46−50 white-light-emitting diodes, 51 and environmental pollution abatement. 52,53 Recently, Li's group employed the silver-based MOG as the solid coreactants to enhance the ECL of Ru(bpy) 3 2+ for DNA assay, with the MOG being used for the loading of Ru(bpy) 3 2+ molecules.…”
mentioning
confidence: 99%
“…55 In addition to transition metal nodes, noble metal ones can also be used to construct metal−organic structures with catalytic or enzyme-mimicking abilities. 56 For instance, Wang et al successfully synthesized a series of coordinated single-atom (Co, Cu, and Au) metal sites with zirconium porphyrinic hollow MOF nanotubes as the supporting matrix. 57 During the synthesis process, the porphyrin molecule not only serves as the bridging linker but also provides a central coordination environment for anchoring and regulating the electronic properties of single metal atoms.…”
Section: Mof-based Metal Doping Strategymentioning
confidence: 99%
“…In a study reported by Hwang and co-workers, they demonstrated that the binding of aliphatic diamines to unsaturated Fe metal nodes in MIL-100­(Fe) can significantly enhance the POD-mimicking catalytic activity of the functionalized MOFs, since the surface with enhanced negative potential could show higher affinity for positively charged TMB . In addition to transition metal nodes, noble metal ones can also be used to construct metal–organic structures with catalytic or enzyme-mimicking abilities . For instance, Wang et al successfully synthesized a series of coordinated single-atom (Co, Cu, and Au) metal sites with zirconium porphyrinic hollow MOF nanotubes as the supporting matrix .…”
Section: Mof-based Metal Doping Strategymentioning
confidence: 99%
“…Metal-organic gels combine the advantages of stimuli-response of physical gels (weak non-covalent interactions) and stability of chemical gels (strong chemical bonds). [1][2][3][4] Metal-organic gels have found applications in various elds such as sensing, [5][6][7][8][9][10] catalysis, [11][12][13][14] environmental remediation, 15,16 renewable energy conversion, [17][18][19] and templates for nanomaterials. 20 Metalorganic framework (MOF)-based gels are particularly interesting because they incorporate MOF nanoparticles with well-dened microporosity in their gel matrix.…”
Section: Introductionmentioning
confidence: 99%